Multi-layer flight control synthesis and analysis of a small-scale UAV helicopter - Karimoddini, Ali; Guowei Cai; Chen, Ben M; Hai Lin; Lee, Tong H (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
In this paper, we present a systematic procedure for the design of a controller for an autonomous helicopter. The studied model of the helicopter is a semi-linearized model, which includes some nonlinear parts that are separated from the linear blocks. The controller structure is a hierarchical controller which consists of two layers: the inner-loop controller that covers the linear parts of the model and the outer-loop controller that handles the nonlinear parts. The inner-loop controller aims at the attitude control of the helicopter and the outer-loop is responsible for its position control. The performance of the designed controller is demonstrated through the simulation and actual flight tests in the hovering situation and the path-tracking mode.